Feasibility of monitoring peripheral blood to detect emerging clones in children with acute lymphoblastic leukemia†. Issue 7 (11th May 2020) - Saliba, Jason; Evensen, Nikki A.; Meyer, Julia A.; Newman, Daniel; Nersting, Jacob; Narang, Sonali; Ma, Xiaotu; Schmiegelow, Kjeld; Carroll, William L.
Abstract: Relapse‐enriched somatic variants drive drug resistance in childhood acute lymphoblastic leukemia. We used digital droplet‐based polymerase chain reaction to establish whether relapse‐enriched mutations in emerging subclones could be detected in peripheral blood samples before frank relapse. Although limitations in sensitivity for some probes hindered detection of certain variants, we successfully detected variants in  NT5C2  and  PRPS1  at a fractional abundance of 0.005% to 0.3%, 41 to 116 days before relapse. As mutations in both these genes confer resistance to thiopurines, early detection protocols using peripheral blood could be implemented to preemptively alter maintenance therapy to extinguish resistant clones before overt relapse.